Silicon-carbon negative electrode material and preparation method and application thereof
By using porous silicon and carbon source carbonization treatment in lithium-ion batteries, a silicon-carbon negative electrode material with a discrete closed-pore structure and a uniform carbon cladding layer is formed, which solves the problems of silicon volume expansion and electrode deformation, and improves the battery Energy density and cycling performance.
Patent Information
- Application Number
- CN202411822876.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-12-12
AI Technical Summary
Graphite, the negative electrode material of traditional lithium-ion batteries, is difficult to meet the range of electric vehicles because its energy density is close to the limit. Due to the high specific capacity but volume expansion, the battery capacity attenuation and safety hazards. The maximum discharge capacity of existing silicon-carbon composite materials is only 1000mAh. /g, it is difficult to meet the needs of higher energy density.
Carbonization is carried out by mixing porous silicon with a carbon source to form a silicon carbon negative electrode material with a discrete closed-porous structure and a uniform dense carbon cladding layer. The porous structure is maintained by one or more carbon claddings and an external dense layer is formed to improve the material's Structural stability and electrochemical properties.
The first discharge capacity, Coulomb efficiency and circulation capacity retention rate of silicon carbon negative electrode materials have been significantly improved, the circulation performance of lithium-ion batteries has been improved, and the problems of silicon volume expansion and electrode deformation have been solved.
Smart Images

Figure CN119315015A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-ion batteries, and in particular relates to a silicon-carbon negative electrode material and a preparation method and application thereof. Background Art
[0002] With the rapid growth of electric vehicles (EVs) in the global market and the increasing requirements for driving range, it is crucial to further improve the energy density of lithium-ion batteries (LIBs) used in electric vehicles. Rechargeable lithium-ion batteries mainly consist of four parts: two electrodes (positive and negative), a separator and an electrolyte, in which the positive and negative electrodes are separated by a separator and a liquid electrolyte, allowing lithium ions to shuttle back and forth between the two electrodes. When the battery is charged, the lithium ions released from the positive electrode will move to the negative electrode. When discharging, the lithium ions will move from the negative electrode to the positive electrode. At the same time, the electrons released by the lithium atoms in the negative electrode will reach the positive electrode through an external circuit, thereby providing electricity through chemical energy.
[0003] The negative electrode material of traditional commercial lithium-ion batteries is mainly graphite material, with a theoretical specific capacity of 372 mAh / g (each six carbon atoms can only accommodate one lithium atom). At present, its actual specific energy density is gradually approaching its theoretical limit, but it is still difficult to meet the needs of the market. Therefore, it is urgent to develop a new generation of high-specific-capacity lithium-ion battery negative electrode materials. Silicon is widely regarded as the most promising negative electrode material for high-energy-density lithium-ion batteries due to its high specific capacity (>3500mAh / g, each silicon atom can bind 4.4 lithium ions) and abundant reserves (the second most abundant element in the earth's crust). However, despite the very high specific capacity of silicon, its huge volume change (>300%) during the lithiation / delithiation process causes serious problems, such as pulverization caused by repeated fracture of silicon, unstable solid electrolyte interface (SEI) and deformation of electrode structure, which will lead to rapid attenuation of battery capacity and decreased cycle performance. In addition, electrode expansion will squeeze the electrolyte filled in the pores of the diaphragm, thereby hindering the transmission of lithium ions. Severe electrode expansion will cause the battery package to bulge, posing a safety hazard. If these challenges are not successfully overcome, silicon can only serve as a limited additive to graphite-based anodes to gradually increase the energy density of lithium-ion batteries.
[0004] In order to solve the serious volume expansion problem of silicon, researchers have proposed some strategies: (1) Nano-sizing of silicon, which overcomes the above problems by reducing volume changes and providing short lithium ion transmission paths. However, nano-silicon negative electrodes face more fundamental problems. The high specific surface area leads to more irreversible reactions and low tap density. (2) Silicon / carbon composite materials. Carbon materials have good conductivity and cycle stability. They can be used as the substrate of silicon materials to effectively inhibit the volume expansion of silicon materials and improve the cycle performance of batteries. However, it is very challenging to obtain the uniformity of silicon particles dispersed in carbon, the uniformity of carbon coating on the surface of silicon particles, and the high conductivity of carbon substrates. (3) Porosification of silicon, which alleviates the volume change of silicon materials by introducing pores. However, the presence of pores may lead to a decrease in the mechanical properties of the material. For example, the material may collapse or break during the slurry and electrode rolling process.
[0005] For example, CN106935834A provides a composite carbon-coated porous silicon negative electrode material, the first layer of which is coated with cracked carbon or graphene of low carbon deposition organic matter, which can well coat or fill porous silicon, and then the second layer of high carbon deposition polymer cracked carbon is coated on its surface, which has the characteristics of being dense, can well improve the conductivity and prevent the electrolyte from entering the interior of the entire particle. Although this solution solves the problems of low coulomb efficiency, poor conductivity, and silicon volume expansion in negative electrode applications of silicon to a certain extent, the maximum discharge capacity of the composite carbon-coated porous silicon negative electrode material of this solution is only 1000mAh / g.
[0006] Therefore, it is necessary to further improve it and develop better silicon-carbon negative electrode materials. Summary of the invention
[0007] The purpose of the present invention is to provide a new silicon-carbon negative electrode material and a preparation method thereof. A lithium-ion battery using the silicon-carbon negative electrode material has a better first discharge capacity, a higher first coulombic efficiency and a more excellent cycle capacity retention rate.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is: The first aspect of the present invention provides a silicon-carbon negative electrode material, comprising porous silicon, a carbon layer filled in the pores of the porous silicon and coated on the outside of the porous silicon; wherein the initial true density of the silicon-carbon negative electrode material is 1.7-2.1 g / cm 3 The change value of the true density after cold pressing at 500MPa is 4~10% compared with the initial true density.
[0009] The initial true density of the silicon-carbon negative electrode material refers to the true density of the silicon-carbon negative electrode material product directly measured without cold pressing.
[0010] The change in true density after cold pressing at 500 MPa compared to the initial true density is calculated as (true density after cold pressing-initial true density) / initial true density×100%.
[0011] According to some specific embodiments, the change in true density after cold pressing at 500 MPa compared to the initial true density is 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6%, 6.1%, 6.2%, 6.3%, 6.4%, 6.5%, 6.6%, 6.7%, 6.8%, 6.9%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6.1%, 6.2%, 6.3%, 6.4%, 6.5%, 6.6%, 6.7%, 6.8%, 6 ... 6%, 6.7%, 6.8%, 6.9%, 7%, 7.1%, 7.2%, 7.3%, 7.4%, 7.5%, 7.6%, 7.7%, 7.8%, 7.9%, 8%, 8.1%, 8.2%, 8.3%, 8.4%, 8.5%, 8.6%, 8.7%, 8.8%, 8.9%, 9%, 9.1%, 9.2%, 9.3%, 9.4%, 9.5%, 9.6%, 9.7%, 9.8%, 9.9% or 10%.
[0012] According to some specific embodiments, the change in true density after cold pressing at 500 MPa is 4-6% compared to the initial true density.
[0013] According to some specific embodiments, the specific surface area of the silicon-carbon negative electrode material is 1 to 20 m 2 / g. Furthermore, the specific surface area of the silicon-carbon negative electrode material is 1-10 m 2 / g, for example 1 m 2 / g, 1.1 m 2 / g, 1.2 m 2 / g, 1.3 m 2 / g, 1.4m 2 / g, 1.5 m 2 / g, 1.6 m 2 / g, 1.7 m 2 / g, 1.8 m 2 / g, 1.9 m 2 / g, 2 m 2 / g, 2.1 m 2 / g, 2.2 m 2 / g, 2.3m 2 / g, 2.4 m 2 / g, 2.5 m 2 / g, 2.6 m 2 / g, 2.7 m 2 / g, 2.8 m 2 / g、2.9 m 2 / g、3m 2 / g、3.1m 2 / g、3.2m 2 / g、3.3m 2 / g、3.4 m 2 / g、3.5m 2 / g、3.6m 2 / g、3.7 m 2 / g、3.8 m 2 / g、3.9 m 2 / g、4 m 2 / g、4.1m 2 / g、4.2m 2 / g、4.3 m 2 / g、4.4 m 2 / g、4.5m 2 / g、4.6 m 2 / g、4.7 m 2 / g、4.8 m 2 / g、4.9 m 2 / g、5m 2 / g、5.1m 2 / g、5.2m 2 / g、5.3m 2 / g、5.4 m 2 / g、5.5m 2 / g、5.6m 2 / g、5.7 m 2 / g、5.8 m 2 / g、5.9m 2 / g、6m 2 / g、6.1m 2 / g、6.2m 2 / g、6.3m 2 / g、6.4 m 2 / g、6.5m 2 / g、6.6m 2 / g、6.7 m 2 / g、6.8m 2 / g、6.9 m 2 / g、7m 2 / g、7.1 m 2 / g、7.2 m 2 / g、7.3 m 2 / g、7.4 m 2 / g、7.5m 2 / g、7.6 m 2 / g、7.7m2 / g, 7.8 m 2 / g, 7.9 m 2 / g, 8 m 2 / g, 8.1 m 2 / g, 8.2 m 2 / g, 8.3 m 2 / g, 8.4 m 2 / g, 8.5 m 2 / g, 8.6m 2 / g, 8.7 m 2 / g, 8.8 m 2 / g, 8.9 m 2 / g, 9 m 2 / g, 9.1 m 2 / g, 9.2 m 2 / g, 9.3 m 2 / g, 9.4 m 2 / g, 9.5m 2 / g, 9.6 m 2 / g, 9.7 m 2 / g, 9.8 m 2 / g, 9.9 m 2 / g or 10 m 2 / g.
[0014] According to some specific embodiments, the carbon content of the silicon-carbon negative electrode material is 20-60wt%, for example, 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt%, 31wt%, 32wt%, 33wt%, 34wt%, 35wt%, 36wt%, 37wt%, 38wt%, 39wt%, 40wt%, 41wt%, 42wt%, 43wt%, 44wt%, 45wt%, 46wt%, 47wt%, 48wt%, 49wt%, 50wt%, 51wt%, 52wt%, 53wt%, 54wt%, 55wt%, 56wt%, 57wt%, 58wt%, 59wt% or 60wt%. Further, the carbon content of the silicon-carbon negative electrode material is 40-50wt%.
[0015] According to some specific embodiments, the oxygen content of the silicon-carbon negative electrode material is less than 10wt%, for example, 10wt%, 9wt%, 8wt%, 7wt%, 6wt%, 5wt%, 4wt%, 3wt%, 2wt%, 1wt%, or even the oxygen content of the silicon-carbon negative electrode material is 0.
[0016] According to some specific embodiments, the silicon carbide content of the silicon-carbon negative electrode material is less than 10wt%, for example, 10wt%, 9wt%, 8wt%, 7wt%, 6wt%, 5wt%, 4wt%, 3wt%, 2wt%, 1wt%, or even the silicon carbide content of the silicon-carbon negative electrode material is 0.
[0017] According to some specific embodiments, the porosity of the silicon-carbon negative electrode material is 5-30%. Among them, the porosity can be inferred from the ratio of the measured true density of the material to the theoretical true density, that is, porosity = (1-measured true density value / theoretical true density) × 100%. The theoretical true density of the material can be calculated from the carbon content, silicon content and theoretical density of carbon and silicon of the material. Due to the presence of internal pores, the measured true density is less than the theoretical true density of the material. Further, the porosity of the silicon-carbon negative electrode material is 13-20%, for example, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5% or 20%.
[0018] According to some specific embodiments, the pores of the silicon-carbon negative electrode material are discrete closed pores. Discrete closed pores refer to multiple pores that are separated from each other and not connected. Discrete closed pores are relative to through pores, and both can be judged by the change in true density before and after the material is crushed. After the material with through pores is crushed, the internal pores can be detected by gas, and the true density will increase significantly. For example, if nitrogen is used for detection, the exposed pores will adsorb nitrogen, and the result may even be negative. However, after the material with discrete closed pores is crushed, only part of the pore structure is exposed, and the degree of change in its true density after crushing is small.
[0019] According to some specific embodiments, the particle size D50 of the silicon-carbon negative electrode material is 1 to 20 microns.
[0020] According to some specific embodiments, the pore size of the internal closed pores of the silicon-carbon negative electrode material is 0.1-5 nm.
[0021] A second aspect of the present invention provides a method for preparing the above-mentioned silicon-carbon negative electrode material, comprising the following steps: (1) mixing porous silicon with a carbon source to obtain a silicon-carbon precursor, and carbonizing the silicon-carbon precursor to obtain a silicon-carbon intermediate; wherein the carbon source is a solid carbon source or a liquid carbon source; (2) The silicon-carbon intermediate is subjected to secondary or multiple carbon coating to obtain the silicon-carbon negative electrode material.
[0022] The purpose of the first carbon coating of porous silicon in step (1) of the present invention is to maintain the structural stability of porous silicon during the high-temperature carbonization process and form a basic structure of discrete closed pores. The purpose of the second or multiple carbon coatings in step (2) is to form a dense coating layer on the outside of the material, further improve the structural stability of the material, and prevent the entry of electrolyte.
[0023] According to some specific embodiments, the peak pore size of the porous silicon is 3-10 nm, such as 3 nm, 3.5 nm, 4 nm, 4.5 nm, 5 nm, 5.5 nm, 6 nm, 6.5 nm, 7 nm, 7.5 nm, 8 nm, 8.5 nm, 9 nm, 9.5 nm or 10 nm. The pore volume of the porous silicon is 0.45-0.75 cm 3 / g, for example 0.45 cm 3 / g, 0.5 cm 3 / g, 0.55 cm 3 / g, 0.6 cm 3 / g, 0.65 cm 3 / g, 0.7 cm 3 / g or 0.75 cm 3 / g. The peak pore size refers to the pore size value that accounts for the largest proportion in the pore size distribution. By using porous silicon with suitable peak pore size and pore volume as raw material, the silicon-carbon negative electrode material prepared according to the above method can obtain an initial true density of 1.7~2.1 g / cm 3 , a silicon-carbon negative electrode material whose true density after cold pressing at 500MPa changes by 4~10% compared to the initial true density. The silicon-carbon negative electrode material with this feature has discrete closed pores, which can provide a buffer for the volume expansion of silicon, thereby improving the cycle capacity retention rate and rate performance of the silicon-carbon negative electrode material, and can also improve the first discharge capacity and first coulombic efficiency of the silicon-carbon negative electrode material.
[0024] According to some specific embodiments, the particle size D50 of the primary particles of the porous silicon is 1-10 nanometers, and the particle size D50 of the secondary particles of the porous silicon is 1-10 micrometers.
[0025] According to some specific embodiments, the porous silicon is obtained by high-temperature disproportionation of silicon oxide and etching with a fluorine-containing reagent, or by etching an aluminum-silicon alloy with hydrochloric acid, or by reducing silicon dioxide with magnesium.
[0026] Furthermore, the specific method for obtaining the porous silicon by high-temperature disproportionation of silicon oxide and etching with a fluorine-containing reagent is as follows: first, silicon oxide (SiOx, 0<x<2) is placed in an atmosphere tube furnace for high-temperature disproportionation reaction to obtain a mixture of silicon and silicon oxide (SiOy, 0<y<=2, y>x); and the obtained mixture is etched with a fluorine-containing reagent to obtain porous silicon.
[0027] Furthermore, the fluorine-containing reagent may be a liquid reagent such as hydrofluoric acid, or a gas phase reagent such as hydrogen fluoride gas.
[0028] Furthermore, the temperature of the high-temperature disproportionation reaction is 800-1200°C.
[0029] Furthermore, the specific method of obtaining the porous silicon from the aluminum-silicon alloy by hydrochloric acid etching is as follows: aluminum-silicon alloy powder with a silicon content of 15wt% to 25wt% is pickled with 15wt% to 25wt% hydrochloric acid for 4 to 6 hours to obtain the porous silicon.
[0030] According to some specific embodiments, the solid carbon source or liquid carbon source is selected from one or more of tar, asphalt, glucose, sucrose, citric acid, and resin.
[0031] According to some specific embodiments, in step (1), the mass ratio of the porous silicon to the carbon source is 1:0.1-2, for example, 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2. Further, the mass ratio of the porous silicon to the carbon source is 1:0.1-1.5. Further, the mass ratio of the porous silicon to the carbon source is 1:0.3-0.8.
[0032] According to some specific embodiments, in step (1), the carbonization temperature is 700-900° C., and the carbonization time is 3-8 hours.
[0033] According to some specific embodiments, the carbon coating in step (2) is the same as the method in step (1), or the carbon coating is performed by decomposing a gas phase carbon source at a high temperature, wherein the flow rate of the gas phase carbon source is 100-300 sccm.
[0034] According to some specific embodiments, the gaseous carbon source is a gaseous hydrocarbon, such as acetylene, ethylene, etc.
[0035] According to some specific embodiments, when carbon coating is performed using a gas-phase carbon source, the flow ratio of the gas-phase carbon source to the inert gas in the introduced mixed gas is 1:2-3.
[0036] Furthermore, the inert gas is one of nitrogen, helium, neon or argon, or a combination thereof.
[0037] A third aspect of the present invention provides an application of the above silicon-carbon negative electrode material in a lithium-ion battery.
[0038] According to some specific embodiments, the method for preparing the negative electrode of the lithium-ion battery includes: first, mixing the silicon-carbon negative electrode material with a binder, a conductive agent, and a solvent in a certain mass ratio to prepare a slurry with a certain viscosity, and then coating the obtained slurry on a current collector by a scraper, and the coating thickness is 20-60 microns. The obtained electrode piece is transferred to a vacuum oven for drying, and the dried electrode piece is cut into a disc with a diameter of 9-15 mm by a cutting machine for assembly of the lithium-ion battery.
[0039] Furthermore, the binder is CMC (hydroxymethyl cellulose), the conductive agent is conductive carbon black (C), the solvent is water; the current collector is copper foil; and the temperature of the vacuum oven is 80-120°C.
[0040] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art: The silicon-carbon negative electrode material of the present invention has multiple discretely distributed closed-pore structures and a uniform and dense carbon coating layer, which can effectively solve the volume expansion problem (>300%) of the silicon negative electrode material during the charging and discharging process of the lithium-ion battery, greatly improve the first discharge capacity, first coulomb efficiency and battery capacity retention rate of the silicon-carbon negative electrode material, and the lithium-ion battery using the silicon-carbon negative electrode material of the present invention has better cycle performance. The preparation method of the silicon-carbon negative electrode material of the present invention is simple in process, and the raw material reserves are abundant and the source is wide. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0042] Figure 1 A schematic diagram of the structure of a silicon-carbon negative electrode material prepared in an embodiment (having a discrete closed-pore structure); Figure 2 A scanning electron microscope image of a cross section of the silicon-carbon negative electrode material prepared in Example 1; Figure 3 A schematic diagram of the structure of the silicon-carbon negative electrode material prepared in Comparative Example 3 (having a through-hole structure and silicon carbide); Figure 4 A schematic diagram of the structure of the silicon-carbon negative electrode material prepared in Comparative Example 6 (without a pore structure); Among them, 1. hole; 2. silicon; 3. carbon layer; 4. silicon carbide. DETAILED DESCRIPTION
[0043] In the following, only some exemplary embodiments are briefly described. As those skilled in the art will appreciate, the described embodiments may be modified in various ways without departing from the spirit or scope of the embodiments of the present invention. Therefore, the drawings and descriptions are considered to be exemplary and non-restrictive in nature.
[0044] All features disclosed in the present invention, or steps in all methods or processes disclosed, except mutually exclusive features or steps, may be combined in any manner.
[0045] The technical solution of the present invention is further described below in conjunction with specific embodiments, but the present invention should not be limited to these embodiments. Unless otherwise described, all can be replaced by other alternative features that are equivalent or have similar purposes. Unless otherwise described, each feature is just an example of a series of equivalent or similar features. The terms used in the present invention, unless otherwise specified, generally have the meanings commonly understood by those of ordinary skill in the art. The implementation conditions used in the embodiments can be further adjusted according to the different requirements of specific use, and the implementation conditions not specified are conventional conditions in the industry. The technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.
[0046] In the present invention, the operation without special instructions is carried out at room temperature. The raw materials in this application can be obtained commercially or prepared by conventional methods in the prior art. In the present invention, unless otherwise specified, the content is mass content, and "%" is mass percentage.
[0047] In the design and selection of negative electrode materials, the present invention takes into account the serious impact of the volume expansion problem (>300%) of silicon negative electrode materials during the charging and discharging process of lithium-ion batteries, as well as the problem that the electrical properties of carbon-coated porous silicon materials still need to be improved. It is unexpectedly found that by using porous silicon of a specific size as raw material and adjusting the ratio of the solid carbon source or liquid carbon source to the porous silicon in the primary carbon coating process, a silicon-carbon negative electrode material intermediate with a discrete closed-pore structure inside can be prepared, and then a secondary carbon coating is performed to form a uniform and dense carbon coating layer, thereby effectively solving the material pulverization and electrode deformation problems caused by the volume change of silicon materials during the charging and discharging process of lithium-ion batteries, improving the electrochemical properties of silicon-carbon negative electrode materials, and the silicon-carbon negative electrode material of the present application has good rate performance and can meet the requirements of rapid charging and discharging of batteries. Among them, the porous silicon of a specific size has a peak pore diameter of 3~10 nanometers and a pore volume of 0.45~0.75 cm 3 / g of porous silicon.
[0048] Furthermore, the pore size of the discrete closed pores inside the silicon-carbon negative electrode material is controlled to be 0.1-5 nanometers to further improve the mechanical and electrochemical properties of the material. If the silicon-carbon negative electrode material does not have discrete closed pores, or has a large number of interconnected through pores, it is not conducive to the electrochemical performance of the material.
[0049] Among them, Figure 2 As shown in the figure, from the scanning electron microscope image, the discrete closed pores inside the silicon-carbon negative electrode material cannot be clearly seen, because the pore size of the closed pores is too small. However, the true density of the silicon-carbon negative electrode material after cold pressing is higher than that before cold pressing, and the increase value is between 4 and 10%, indicating that there are pores inside the silicon-carbon negative electrode material. Combined with the scanning electron microscope images of multiple different cross-sections of the silicon-carbon negative electrode material by the applicant, no obvious pores were observed. It can be inferred that the silicon-carbon negative electrode material of the present application has discrete closed pores with a pore size of less than 5nm.
[0050] Furthermore, the particle size D50 of the primary particles of the porous silicon is 1-10 nanometers, and the particle size D50 of the secondary particles of the porous silicon is 1-10 micrometers. The primary particles of the porous silicon refer to the size of a single solid particle inside the porous silicon, i.e. Figure 1 The size of the silicon particle with the number 2 shown. The pore size of porous silicon refers to the pore size in the secondary particles formed by connecting multiple primary particles together, that is, the gap between multiple primary particles. The porous silicon secondary particles refer to porous silicon particles separated from each other. Example 1
[0051] 1. Preparation of silicon-carbon negative electrode materials: (1) Place 10 g of silicon monoxide in an atmosphere tube furnace, introduce argon protective gas into the tube furnace, and treat at 900°C for 5 hours. Silicon monoxide undergoes a disproportionation reaction at high temperature to generate a mixture of silicon and silicon dioxide; (2) The above mixture was added to a 49% hydrofluoric acid aqueous solution and stirred to remove the silicon dioxide, and then washed and dried with deionized water to obtain porous silicon. The secondary particle size D50 of the porous silicon was 5.2 μm, the primary particle size D50 was 3.8 nm, the peak pore size of the porous silicon was 3.7 nm, and the pore volume of the porous silicon was 0.7 cm 3 / g; (3) placing porous silicon and asphalt acetone solution in a stirring kettle, wherein the mass ratio of porous silicon to asphalt is 1:0.5, stirring thoroughly and drying to obtain a silicon-carbon precursor; (4) placing the silicon-carbon precursor in an atmosphere tube furnace, introducing argon protective gas into the tube furnace, and subjecting the precursor to high-temperature treatment at 800°C for 5 hours. The asphalt material is carbonized at high temperature to form a carbon layer on the porous silicon, thereby obtaining a silicon-carbon intermediate; (5) Repeat steps (3) and (4) for the silicon-carbon intermediate obtained in the previous step to obtain the final product, a silicon-carbon negative electrode material.
[0052] 2. Preparation of lithium-ion half-cell: The silicon-carbon negative electrode material, conductive carbon black and binder are added to an appropriate amount of deionized water in a mass ratio of 8:1:1 to prepare a slurry, and the obtained slurry is coated on a copper foil by an adjustable scraper to prepare a battery electrode. The coated electrode is dried in an oven at 80°C for 2 h, and then taken out and cut into negative electrode electrodes with a diameter of 15 mm by an electrode cutter. The cut electrode is placed in a vacuum drying oven at 120°C and dried for 5 h; The dried electrode was quickly transferred to a glove box filled with argon (water and oxygen contents were less than 0.1 ppm), a metal lithium sheet was used as the counter electrode, the electrolyte was a mixed solvent containing 1 M LiPF6 (EC / EMC 3:7 v / v), and the separator was a polypropylene (PP) film, and the lithium-ion half-cell was assembled; The assembled battery was left to rest for 12 h, and then a 0.1 C constant current charge and discharge test was performed on the Blue Power Battery Test System with a voltage range of 0.01-1.5 V. Rate test: The half-cell was discharged at 0.1C and charged at 0.1C and 2C respectively. The ratio of the capacity obtained at 2C / the capacity obtained at 0.1C was used to represent the rate performance of the material.
[0053] 3. Preparation of lithium-ion full battery: The commercial ternary NMC532 was used as the positive electrode, the prepared silicon-based material was used as the negative electrode, the electrolyte was a mixed solvent containing 1 MLiPF6 (EC / EMC 3:7 v / v, 10% FEC), and the diaphragm was a polypropylene (PP) film to assemble the lithium-ion full battery. The assembled battery was left to stand for 12 hours, and then a 0.33C constant current and constant voltage charge and discharge test was performed on the Blue Electric Battery Test System, with a voltage range of 2.5-4.2v. Example 2
[0054] The other steps are the same as those in Example 1, except that the mass ratio of porous silicon to asphalt is 1:1. Example 3
[0055] The other steps were the same as those in Example 1, except that the secondary carbon coating was performed in a mixed gas of acetylene (200 sccm) and nitrogen (500 sccm), at a temperature of 800° C., for 3 hours. Example 4
[0056] The other steps are the same as those in Example 1, except that the heat treatment temperature of silicon monoxide in step (1) is 1000°C, the particle size D50 of the secondary particles of the porous silicon obtained is 5.2 μm, the particle size D50 of the primary particles is 8.0 nm, the peak pore size of the porous silicon is 5.9 nm, and the pore volume of the porous silicon is 0.5 cm 3 / g. Example 5
[0057] The other steps are the same as those in Example 1, except that the porous silicon is obtained by pickling the aluminum-silicon alloy powder with a silicon content of 20 wt% with 20 wt% hydrochloric acid for 5 h. The secondary particle size D50 of the porous silicon is 7.2 μm, the primary particle size D50 is 5.8 nm, the peak pore size of the porous silicon is 8.1 nm, and the pore volume of the porous silicon is 0.7 cm 3 / g. Example 6
[0058] The other steps are the same as those in Example 1, except that the carbon source for carbon coating is glucose. Comparative Example 1
[0059] The other steps are the same as those in Example 1, except that the material is not etched with hydrofluoric acid and is not subjected to secondary carbon coating, that is, step (2) and step (5) in Example 1 are omitted. Comparative Example 2
[0060] The other steps are the same as those in Example 1, except that the material is not subjected to secondary carbon coating, that is, step (5) in Example 1 is omitted. Comparative Example 3
[0061] The other steps are the same as those in Example 1, except that the porous silicon is carbon coated only once, and the process is carried out in a mixed gas of acetylene (200 sccm) and nitrogen (500 sccm), at a temperature of 800° C., for 5 hours. Comparative Example 4
[0062] The other steps are the same as those in Example 1, except that the porous silicon is carbon-coated only once, and the process is carried out in a mixed gas of acetylene (200 sccm) and nitrogen (500 sccm), at a temperature of 600° C., for 5 hours. Comparative Example 5
[0063] The other steps are the same as those in Example 1, except that the primary carbon coating of porous silicon is carried out in a mixed gas of acetylene (200 sccm) and nitrogen (500 sccm) at a temperature of 700°C for 1 hour, and the secondary carbon coating uses asphalt, wherein the mass ratio of porous silicon to asphalt is 1:0.5, the temperature is 800°C, and the time is 3 hours. Comparative Example 6
[0064] The other steps are the same as those in Example 1, except that the precursor of porous silicon is SiO 1.5 The mass ratio of porous silicon to asphalt is 1:2.5, wherein the particle size D50 of the secondary particles of the porous silicon is 6.7 microns, the particle size D50 of the primary particles is 3.5 nanometers, the peak pore size of the porous silicon is 6.3 nanometers, and the pore volume of the porous silicon is 0.8 cm 3 / g. Comparative Example 7
[0065] The other steps are the same as those in Example 5, except that the silicon content of the silicon-aluminum alloy powder is 10 wt %. The particle size D50 of the secondary particles of the porous silicon obtained is 6.2 μm, the particle size D50 of the primary particles is 4.5 nm, the peak pore size of the porous silicon is 20.3 nm, and the pore volume of the porous silicon is 0.9 cm 3 / g.
[0066] Performance testing: The test method for specific surface area, pore size and pore volume is as follows: measured using Guoyi Quantum V-SORP 2800P.
[0067] The carbon content is tested by heating the sample in a muffle furnace to oxidize the carbon in the sample into carbon dioxide and the silicon into silicon dioxide. The mass of silicon dioxide can be used to calculate the silicon content in the original sample, and then the carbon content can be calculated.
[0068] Testing method for silicon carbide content: The silicon carbide content is determined by the peak value of silicon carbide in the X-ray diffraction spectrum.
[0069] Test method for oxygen content: oxygen content is obtained by EDS energy spectrum analysis.
[0070] Primary particle size test method: measured using Dandong Bettersize2600 laser particle size analyzer.
[0071] Secondary particle size test method: calculated by Scherrer formula based on the intensity of silicon diffraction peak in the X-ray diffraction spectrum.
[0072] Calculation method of porosity: Porosity can be estimated from the ratio of measured true density of the material to theoretical true density, that is, porosity = (1-measured true density value / theoretical true density) × 100%. The theoretical true density of the material can be calculated from the carbon content, silicon content and theoretical density of carbon and silicon.
[0073] The test method for the true density of the original material is: use the Guoyi Quantum G-DenPyc X900 to measure the true density of the material.
[0074] The test method for the true density of the material after cold pressing at 500MPa is as follows: put 0.5g of the material into a mold with a diameter of 1.5cm, pressurize it to 500MPa, maintain it for 30s, and then release the pressure. Take out the material and perform the true density test according to the above true density test method.
[0075] The test results of the performance parameters of the above embodiments and comparative examples are shown in Table 1. The first discharge (delithiation) capacity, first coulomb efficiency and cycle capacity retention rate of the above embodiments and comparative examples are shown in Table 2. The rate performance test results of some embodiments and comparative examples are shown in Table 3.
[0076]
[0077]
[0078]
[0079] Compared with Example 1, the asphalt content in Example 2 is increased, and the carbon content in the obtained product is increased accordingly, the first discharge capacity and efficiency are reduced, but the cycle capacity retention rate is improved. In Example 3, the secondary carbon coating is carried out using a gas-phase carbon source, which can achieve similar effects as in Example 1, and the obtained product has similar capacity, efficiency and discrete closed-pore structure. In Example 4, the treatment temperature of silicon monoxide is increased, resulting in changes in the pore structure of the generated porous silicon, which can regulate the true density of the final product, but the porosity of the negative electrode material obtained in Example 4 is smaller than that of other embodiments. Therefore, it is impossible to provide sufficient space for the volume expansion of the silicon material, resulting in the cycle capacity retention rate of Example 4 being inferior to that of other embodiments. Example 5 and Example 6 use different silicon sources and carbon sources, respectively, which can achieve similar effects as Example 1.
[0080] Comparative Example 1 does not undergo hydrofluoric acid etching or secondary carbon coating, and the resulting product is a mixture of carbon-coated silicon and silicon dioxide. The presence of silicon dioxide results in lower capacity and efficiency. Comparative Example 2 does not undergo secondary carbon coating, and the carbon layer of the resulting product is loose and porous, resulting in an increase in specific surface area, reducing the initial coulombic efficiency, and the electrolyte is easily in contact with the internal silicon to produce side reactions, resulting in a significant decrease in the cycle capacity retention rate and rate performance. Comparative Example 3 uses acetylene as the single carbon source. Since acetylene decomposes into a strongly exothermic reaction, and the acetylene decomposition product has high activity, silicon carbide is generated; in addition, during the carbon coating process, the acetylene decomposition product enters the porous silicon structure from the outside to the inside, resulting in more carbon deposition on the outside, blocking the pores of the porous silicon in the early stage of carbon coating, thereby forming a pore structure with through holes. The negative electrode material with such a pore structure has low mechanical strength, and its specific surface area will increase significantly after the material is broken, resulting in problems such as decreased efficiency. Comparative Example 4 uses acetylene as a single carbon source and uses a lower carbon coating temperature. Although low-temperature carbon coating avoids the formation of a large amount of silicon carbide, the coating formed at low temperature has a high degree of amorphism and low conductivity, resulting in a decrease in material performance. Comparative Example 5 uses acetylene for a single carbon coating at 700 ° C. The reaction activity of acetylene is high. During the single carbon coating, the primary particles of silicon will grow significantly, resulting in a decrease in material performance. The asphalt content in Comparative Example 6 is further increased, and the carbon content of the resulting product is increased, resulting in the pores inside the porous silicon being filled, and the material does not have a discrete closed-cell structure, resulting in a decrease in the first discharge capacity, first coulomb efficiency, and cycle capacity retention rate of the negative electrode material. The peak pore size of the porous silicon in Comparative Example 7 is too large, resulting in a large internal pore size after carbon coating, a connected structure is formed between the pores, and the rupture after cold pressing causes the internal pores to be exposed, resulting in a decrease in the first coulomb efficiency and cycle capacity retention rate of the negative electrode material.
[0081] There is a discrete closed-pore structure in the silicon-carbon negative electrode materials of Examples 1 to 6. Therefore, after the material is cold-pressed at 500 MPa, only part of the closed pores are opened, and most of the closed pores still exist. The true density change after cold pressing is less than 10%, and more preferably less than 6%. However, Comparative Examples 1 and 6 do not have a porous structure, and Comparative Example 2 itself is loose and porous. Therefore, the true density of Comparative Examples 1 and 2 does not change before and after cold pressing. Comparative Examples 3 to 5 and Comparative Example 7 are all through-hole pore structures. Therefore, after cold pressing, the pores are opened, resulting in a large change in true density after cold pressing.
[0082] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A silicon-carbon negative electrode material, characterized in that: The invention comprises porous silicon, a carbon layer filling the pores of the porous silicon and coating the outside of the porous silicon; wherein the initial true density of the silicon-carbon negative electrode material is 1.7-2.1 g / cm 3 The change value of the true density after cold pressing at 500MPa is 4~10% compared with the initial true density.
2. The silicon-carbon negative electrode material according to claim 1, characterized in that: The change in true density after cold pressing at 500 MPa compared to the initial true density is 4-6%.
3. The silicon-carbon negative electrode material according to claim 1, characterized in that: The specific surface area of the silicon-carbon negative electrode material is 1-20 m 2 / g; the carbon content of the silicon-carbon negative electrode material is 20~60wt%.
4. The silicon-carbon negative electrode material according to claim 3, characterized in that: The specific surface area of the silicon-carbon negative electrode material is 1-10 m 2 / g; the carbon content of the silicon-carbon negative electrode material is 40~50wt%.
5. The silicon-carbon negative electrode material according to claim 1, characterized in that: The porosity of the silicon-carbon negative electrode material is 5-30%.
6. The silicon-carbon negative electrode material according to claim 5, characterized in that: The porosity of the silicon-carbon negative electrode material is 13-20%.
7. The silicon-carbon negative electrode material according to claim 1, characterized in that: The oxygen content of the silicon-carbon negative electrode material is less than 10 wt %, and the silicon carbide content of the silicon-carbon negative electrode material is less than 10 wt %.
8. The silicon-carbon negative electrode material according to claim 1, characterized in that: The pores of the silicon-carbon negative electrode material are discrete closed pores.
9. The silicon-carbon negative electrode material according to claim 1, characterized in that: The particle size D50 of the silicon-carbon negative electrode material is 1-20 micrometers, and the pore size of the internal closed pores of the silicon-carbon negative electrode material is 0.1-5 nanometers.
10. A method for preparing a silicon-carbon negative electrode material according to any one of claims 1 to 9, characterized in that: The steps include: (1) mixing porous silicon with a carbon source to obtain a silicon-carbon precursor, and carbonizing the silicon-carbon precursor to obtain a silicon-carbon intermediate; wherein the carbon source is a solid carbon source or a liquid carbon source; (2) Carrying out carbon coating on the silicon-carbon intermediate twice or multiple times to obtain the silicon-carbon negative electrode material.
11. The method for preparing the silicon-carbon negative electrode material according to claim 10, characterized in that: The peak pore size of the porous silicon is 3-10 nanometers, and the pore volume of the porous silicon is 0.45-0.75 cm 3 / g.
12. The method for preparing the silicon-carbon negative electrode material according to claim 10, characterized in that: The particle size D50 of the primary particles of the porous silicon is 1 to 10 nanometers, and the particle size D50 of the secondary particles of the porous silicon is 1 to 10 micrometers.
13. The method for preparing the silicon-carbon negative electrode material according to claim 10, characterized in that: The porous silicon is obtained by high-temperature disproportionation of silicon oxide and etching with a fluorine-containing reagent, or by etching an aluminum-silicon alloy with hydrochloric acid, or by reducing silicon dioxide with magnesium.
14. The method for preparing the silicon-carbon negative electrode material according to claim 10, characterized in that: The solid carbon source or liquid carbon source is selected from one or more of tar, asphalt, glucose, sucrose, citric acid and resin.
15. The method for preparing the silicon-carbon negative electrode material according to claim 10, characterized in that: In step (1), the mass ratio of the porous silicon to the carbon source is 1:0.1-2.
16. The method for preparing the silicon-carbon negative electrode material according to claim 10, characterized in that: In step (1), the carbonization temperature is 700-900° C., and the carbonization time is 3-8 hours.
17. The method for preparing the silicon-carbon negative electrode material according to claim 10, characterized in that: The carbon coating in step (2) is the same as the method in step (1), or the carbon coating is performed by decomposing a gas phase carbon source at a high temperature, wherein the flow rate of the gas phase carbon source is 100-300 sccm.
18. The method for preparing the silicon-carbon negative electrode material according to claim 17, characterized in that: The gaseous carbon source is a gaseous hydrocarbon.
19. Use of the silicon-carbon negative electrode material according to any one of claims 1 to 9 in a lithium-ion battery.
Citation Information
Patent Citations
Preparation method of lithium ion battery porous silicon carbon composite negative material
CN102709565A
Silicon-carbon composite anode material for lithium ion battery and preparation method thereof
CN110400927A
Expanded composite microsphere as well as preparation method and application thereof
CN115845754A
Silicon-carbon composite material as well as preparation method and application thereof
CN116487577A
Porous silicon carbon composite, method for preparing same, and anode active
CN118613929A
Cited By
Preparation method of high-capacity silicon-carbon negative electrode material
CN120057924A
Modified porous silicon material, preparation method thereof and application of modified porous silicon material in lithium ion battery
CN121905846A
A modified porous silicon material, a method for preparing the same and application thereof in lithium ion batteries
CN121905846B